Does The Merger of Large Sharia Bank Work? A Study of Islamic Bank in Indonesia - Moza Audina Sopharia; Pupung Purnamasari; Innez Assyffa Andien Wahyuningtyas (International Journal of Emerging Issues in Islamic Studies, 2024)
In 2021, the Indonesian government merged three major state-owned Islamic banks to support the halal industry in the country. Numerous studies have analyzed balance sheet ratios to assess the conditions of Bank Syariah Indonesia (BSI) before and after the merger. However, the reliability of balance sheet ratios is highly contingent on the accounting method employed by companies. Consequently, this study utilizes Economic Value Added (EVA) to measure BSI's financial performance before and after the merger. The primary objective of this research is to test and provide empirical evidence regarding the effectiveness of the EVA approach in demonstrating the economic added value to BSI throughout the merger. Employing a quantitative approach and secondary data from the financial statements of BSI before and after the merger serves as the data source. The findings reveal that the financial performance of BSI before and after the merger provides economic added value to the company and aligns with stakeholder expectations. Notably, research on financial performance using EVA at BSI before and after the merger is scarce, as most studies resort to ratio analysis for this purpose. It is important to acknowledge the limitations of this research, which solely introduces EVA to assess the economic added value in financial statements. Other approaches beyond ratio analysis can be explored to measure the quality of financial statements.